2013
DOI: 10.1093/mnras/stt641
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the three-dimensional structure in the central region of the supernova remnant SNR 0540−69.3★

Abstract: We present and discuss new visual wavelength-range observations of the inner regions of the supernova remnant SNR 0540-69.3 that is located in the Large Magellanic Cloud (LMC). These observations provide us with more spatial and spectral information than were previously available for this object. We use these data to create a detailed three-dimensional model of the remnant, assuming linear expansion of the ejecta. With the observations and the model we study the general three-dimensional structure of the remna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(71 citation statements)
references
References 45 publications
(45 reference statements)
9
62
0
Order By: Relevance
“…In addition to the small-scale asymmetries in the form of rings and clumps, the inner ejecta of SNR 0540 show a global asymmetry in the sense that the redshifted ejecta have higher fluxes and higher velocities than the blueshifted side. This has been noted in previous observations (Kirshner et al 1989;Serafimovich et al 2005;Morse et al 2006;Sandin et al 2013) and is likely caused by asymmetries in the explosion and/or the energy input from the pulsar. Net motion of the progenitor relative to the local ISM may also play a role in explaining this asymmetry, as originally discussed by Kirshner et al (1989).…”
Section: The Innermost Regionsupporting
confidence: 71%
See 2 more Smart Citations
“…In addition to the small-scale asymmetries in the form of rings and clumps, the inner ejecta of SNR 0540 show a global asymmetry in the sense that the redshifted ejecta have higher fluxes and higher velocities than the blueshifted side. This has been noted in previous observations (Kirshner et al 1989;Serafimovich et al 2005;Morse et al 2006;Sandin et al 2013) and is likely caused by asymmetries in the explosion and/or the energy input from the pulsar. Net motion of the progenitor relative to the local ISM may also play a role in explaining this asymmetry, as originally discussed by Kirshner et al (1989).…”
Section: The Innermost Regionsupporting
confidence: 71%
“…For the [S II] emission, we take the ratio I([S II] λ6731)/I([S II] λ6716) = 1.0, which is close to the average number of Serafimovich et al (2005) and Sandin et al (2013). We will investigate possible spatial variations of this line ratio in future work.…”
Section: Construction Of Emissivity Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of Sk−69 202's CSM is almost identical to the CSM of Sher 25, a Galactic B1.5 I supergiant (Brandner, Chu, Eisenhauer, et al 1997). Interestingly, the second youngest CCSNR in the LMC, 0540−69.3, also shows a [N II] ring around the SN that corresponds to a CSM similar to that around Sk−69 202 or Sher 25 (Caraveo, Mignani, & Bignami 1998;Sandin, Lundqvist, Lundqvist, et al 2013).…”
Section: Csi In Core-collapse Snrsmentioning
confidence: 69%
“…The elongation was initially thought (Gotthelf & Wang 2000) to be a jet, but high-resolution optical imaging (Morse et al 2006) showed a diffuse "breakout" instead of a collimated jet in this region. More recent analysis (Sandin et al 2013) has suggested that this elongation may actually be a torus around the pulsar, similar to the X-ray torus around the Crab (Figure 1.5), with a jet pointing to the southwest.…”
Section: Morphology 631 X-ray Morphologymentioning
confidence: 64%